Integration of Autogenic Exercise and Murrotal Al-Quran Improves the Quality of Life of the Elderly: A Quasy Experimental Study - Gunardi Pome; I Gusti Ayu Putu Desy Rohana; Eva Luthfiati Putri; Muhamad Jauhar (Jurnal Berita Ilmu Keperawatan, 2025)
The rising number of older adults in Indonesia, particularly those living with non-communicable diseases (NCDs) like diabetes mellitus (DM), presents significant challenges in enhancing their quality of life. This study investigates the impact of combining autogenic exercise with Al-Quran murottal on the quality of life among the elderly with DM. Employing a quasi-experimental design with a pre- and post-test approach, the research involved 89 elderly participants who met the inclusion criteria. These participants were divided into two groups: an intervention group, which received regular sessions of autogenic training combined with Al-Quran murottal, and a control group, which practiced self-directed internalization. The WHOQOL-OLD instrument was used to assess quality of life, with data analyzed using paired t-test and independent t-test. The findings revealed a significant improvement in the quality of life for the intervention group, as reflected by an increase in the average score from 49.42 to 74.72 (p < 0.05). Conversely, the control group experienced a minor, statistically insignificant decline in quality of life. These results demonstrate that integrating physical and spiritual elements, such as autogenic exercises and Al-Quran murottal, effectively enhances the quality of life for older adults with DM, offering a holistic approach to improving their well-being.